IMPLEMENTATION OF MINIMUM STOCK DETERMINATION USING PREDICTION AND ECONOMIC ORDER QUANTITY (EOQ) METHOD - Pinem, Kelvin Fernando; Mulyawan, Bagus; Perdana, Novario Jaya (Jurnal Ilmu Komputer dan Sistem Informasi, 2021)
In an effort to get competitive prices, one must be able to organize the planning of the availability of the goods it owns so that it can maintain a balance between demand and the existing stock of goods (supply). This application aims to create a precise forecasting system that is useful for determining the inventory of goods in stock that must be done in accordance with the old sales data that have occurred. The method used in this research is forecasting to predict or predict the inventory of goods, then calculating the Economic Order Quantity (EOQ) to return the number of items ordered which will ultimately reduce the cost of inventory. The forecasting method used is Single Exponential Smoothing (SES), Double Exponential Smoothing (DES). The results of data testing on the Forecast method using Forecasting used are Single Exponential Smoothing (SES) and Double Exponential Smoothing (DES). The smallest MAD results were obtained from each of the Forecast methods. After forecasting, the best forecasting method will be chosen which has the value of Mean Absolute Deviation (MAD), mean quality squared (Mean Square Error), the proportion of mean absolute error (Mean Absolute Percentage Error). This Economic Order Quantity (EOQ) method helps to determine the optimal purchase frequency. How to determine and the optimal frequency of purchases.